Policy of Russia in the Former Soviet Union after Return of the Crimea: Challenges and Priorities - Irina Nikolaevna Novikova; Vladimir Germanovich Burkov; Konstantin Evgenyevich Meshcheryakov (Управленческое консультирование)
Return of the Republic of Crimea and Sevastopol under the sovereignty of the Russian Federation became the major event not only for our country, but also in universal scale. It had essential impact on modern system of the international relations. Considerable changes occurred and in foreign policy of Russia in the former Soviet Union - the region which is permanently playing a key role in system of national priorities of the Russian Federation. In the conditions of opposition of Russia and the countries of the West a number of the States of the region hurried to separate from Moscow or, at least, to take a neutral position on the Ukrainian crisis and «The Crimean question». Other republics rallied with Russia even more closely, giving it the increasing support in the international affairs. In this article the main achievements and miscalculations of domestic diplomacy in the former Soviet Union during its «Post-Crimean» period - in 2014 - the first half of 2015 come to light.